Application of Digital Technology Risk Management Models in Banking Institutions Reflecting The Digital Transformation of Indonesian Banking BLUEPRINT - Kento Mazayo; Sri Agustina; Riska Asri (International Institute for Advanced Science & Technology (IIAST), 2023)
This article discusses trends in the use of digital technology in the banking industry that are occurring in the world, specifically in Indonesia. This study found that the use of digital technology (digitization) has made the global financial ecosystem change rapidly. This happens because people's demand for digital services continues to increase. This opens up opportunities for the banking industry to increase the number of customers and increase profits. However, on the other hand, there are a number of channels through which banking institutions have the potential to experience potential losses because cybercrime will continue to increase. The authors therefore suggest that banking institutions continue to seek to reinvent their risk management function, especially through the development of digital risk management, to protect themselves, their customers and their place in the market. In Indonesia, the Financial Services Authority (OJK) has actually created a blueprint and road map that helps the banking industry implement digitalization and develop digital risk management in a targeted and effective manner.